A NUMERICAL INVESTIGATION OF EFFECTS OF THE INLET VELOCITY MAGNITUDE ON THE AIRBORNE CONTAMINANTS REMOVAL FROM A CLEANROOM SPACE TAKING INTO ACCOUNT OPERATOR’S MOVEMENT - Evgeny V. Cherniakov (Вестник Северо-Кавказского федерального университета)
This study deals with the influence of the inlet airflow velocity on the efficiency of the airborne particles removal from a cleanroom area, taking into account moving (operator) and motionless (worktable) objects which are presented in a cleanroom.